Functional consequences of alder and oak loss in stream ecosystems. (19th July 2022) - Alonso, Alberto; López‐Rojo, Naiara; Pérez, Javier; Boyero, Luz
Abstract: Alder ( Alnus glutinosa ) and oak ( Quercus robur ) are dominant tree species in European Atlantic mixed forests, and their leaf litter is a key resource for stream ecosystems. While alder litter has higher nutrient content and palatability than other species and is rapidly processed in the stream by detritivores and microorganisms, oak litter is a tougher and less nutritious but more persistent resource. Given that both species are declining due to the spread of the fungal pathogens Phytophthora alni and Phytophthora cinnamomi, respectively, we investigated how their reduction or loss might alter stream ecosystem functioning through changes in litter decomposition, invertebrate detritivore ( Sericostoma pyrenaicum ) growth and stoichiometry, and fungal decomposer assemblage characteristics. We conducted a microcosm experiment where we incubated litter mixtures representing different scenarios of alder and oak reduction or loss (and a concomitant increase in the other species), compared to a control that contained the four most common species in the study area (alder, oak, hazel [ Corylus avellana ] and willow [ Salix atrocinerea ]) in the same proportions as found in nature. The experiment lasted for 9 weeks, with the above variables measured every 3 weeks. Decomposition rates changed depending on which species was lost. Rates decreased as a result of alder loss and increased following oak loss. Sericostoma nutrient assimilation also responded to species loss, increasing and decreasing following alder and oak loss, respectively, possibly due to compensatory assimilation. Differences in Sericostoma nutrient concentrations among treatments decreased with time in the case of nitrogen, whereas they increased for phosphorus, probably due to microbial colonisation. The presence of oak also constrained microbial activity at the end of the experiment, reducing sporulation rates and causing differences in assemblage structure, probably due to inhibitory traits such as tannins or phenolic compounds. Treatments examining the loss of both species did not differ from the control, either in decomposition or sporulation rate, since loss of both alder and oak counteracted their effects. However, sporulation rates were higher for the scenario with loss of both species than for treatments with either alder reduction or loss, whereas sporulation rate and assemblage structure in the treatment with loss of both species were similar to the scenarios with oak reduction and loss, indicating that oak loss is more important for microbial activity. Changes in nutrient assimilation throughout the experiment suggested that effects of plant species reduction and loss can alter ecosystem functioning depending not only on litter palatability, but also on detritivore life stage. Overall, our results provide evidence for the importance of maintaining native riparian vegetation to preserve various ecosystem functions.